Influencing Factors Of Green Marketing, Environmentalist Communities, And Key Opinion Leaders On Conscious Buying Behavior In Indonesia - Elisabet Iskandar; I Gede Sanica (UNIVED Press, 2024)
In recent years, there has been a concerning surge in the volume of waste generated by the population in the country. This research primarily aims to pinpoint the pivotal factors that drive a shift in societal behavior towards conscious buying habits. The study involved 113 respondents from the millennial demographic residing or working in the Tangerang city area. The collection of data was conducted through the distribution of questionnaires utilizing the Google Form platform. The data analysis method employed was Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results revealed that factors such as green marketing, engagement in environmental communities, and knowledge about environmental issues consistently and significantly influence conscious buying behavior. However, the impact of key opinion leaders did not show a significant influence in altering this behavior. These findings offer a comprehensive insight into how specific factors shape environmentally conscious purchasing behavior. The implications of this research can serve as a foundation for more effective initiatives aimed at educating and guiding society towards more environmentally responsible behaviors through tailored marketing strategies